(2x-5)=(x+30)

Simple and best practice solution for (2x-5)=(x+30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-5)=(x+30) equation:


Simplifying
(2x + -5) = (x + 30)

Reorder the terms:
(-5 + 2x) = (x + 30)

Remove parenthesis around (-5 + 2x)
-5 + 2x = (x + 30)

Reorder the terms:
-5 + 2x = (30 + x)

Remove parenthesis around (30 + x)
-5 + 2x = 30 + x

Solving
-5 + 2x = 30 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-5 + 2x + -1x = 30 + x + -1x

Combine like terms: 2x + -1x = 1x
-5 + 1x = 30 + x + -1x

Combine like terms: x + -1x = 0
-5 + 1x = 30 + 0
-5 + 1x = 30

Add '5' to each side of the equation.
-5 + 5 + 1x = 30 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = 30 + 5
1x = 30 + 5

Combine like terms: 30 + 5 = 35
1x = 35

Divide each side by '1'.
x = 35

Simplifying
x = 35

See similar equations:

| 2(v-4)=8v+34 | | -2xy*3xy= | | 8-4x-(12-3x)= | | 80-(4x+7)=4(x+7)+x | | 2(2x-1)=3(x+1) | | x+73x=77 | | 6b^2+19b-36=0 | | 6(d+6)=4(d-6)-d | | -24(x-2)= | | 2(n+4)=8-6(n-4) | | -24(x+2)= | | -12(2x-12)= | | 2x-2y=-1 | | m+m(0.07)= | | 2x-3y+x+5y-3= | | y=5x-13 | | (57x+58y)+(-5x+41y)= | | (18x+2y)+(36x+27y)= | | (63x+50y)-(17x+35y)= | | (64x+48y)-(9x-16y)= | | 5x-3=-10x+8 | | 2x+8=-28 | | (30+5x)+(15+10x)=180 | | 6x+5=9x-19 | | 64-7x=2x+17 | | 2x+3x+1=12-6 | | 6x+14=-40 | | 8-9[9-(3y-7)]= | | 6-9x=29-16x | | 61-7x=11x+23 | | 13-8x=39-22x | | 6-9x=29-6x |

Equations solver categories